Análise da expressão gênica de Anopheles darlingi (Diptera, Culicidae) em condições naturais e no laboratório sob estresse produzido pelo petróleo - Rocha, Marla Raquel Pontes da (2012)
Gene expression studies in mosquitoes have given relevant information on the implementation of vector control strategies. The profile of gene expression can be modified by environmental factors and one example is the petroleum which has toxic organic compounds in its composition being therefore a stressor agent. Petroleum exploration in the Amazon region is growing and in the municipality of Coari-AM is located the Urucu petroliferous province with intense oil exploration and refined petroleum products. In this work, the petroleum was analyzed as a stressor agent to Anopheles darlingi Root, 1926, the main vector of human malaria in the Amazon. For this, larvae of A. darlingi were collected from riverine habitats near the east zone of Manaus town. The stress effects of petroleum were evaluated by gene expression analyzes in larvae of A. darlingi under natural conditions and stress exposure. Toxic bioassays were developed with the objective to establish an experimental design of CL50 and then proceed to the molecular analyzes. For gene expression evaluation cDNA libraries were constructed and sequencing was established by Sanger sequencing and Transcriptome Sequencing (RNA-seq) to obtain Expressed Sequence Tags (ESTs). The data from the gene expression profiles of cDNA libraries from control (larvae in natural conditions) and treatment (larvae under petroleum stress) were analyzes by the bioinformatic program BLAST2GO. In the bioassays of CL50 the concentrations were determined at 0.32 ppm and 0.06 ppm which the larvae of A. darlingi was subjected to stress for further gene expression analyzes. The obtained results showed the representativity of ESTs from the control and treatment libraries. Among the differentially expressed genes in the treatment were the family hsp known by encoding proteins involved in thermal shock, the enzymatic group tps responsible by the terpene biosynthesis and the ctnb related to the oxidoreductase biosynthesis, being all related to stress caused by petroleum. These genes are related to detoxification of organism metabolism indicating important processes of pesticide resistance and the tps can be considered as a marker of exposure to petroleum. In addition to the genes differentially expressed in the treatment, the gly gene was observed and is related to the transcription of glycine-rich proteins (GRPs), and as it was expressed in both libraries it has the possibility of being a normalize for both conditions. Therefore, the observed parameters of gene expression in larvae of A. darlingi establish new perspectives to the species functional genomics. Key-words: Anopheles darlingi; Gene expression; Sanger-CE; NGS-RNAseq; Petroleum; Environmental stress